A Sinicised Religion Under Foreign Rule: Buddhism in the Jurchen Jin Dynasty (1115–1234). (May 2019) - Lin, Hang
Buddhism in the Jurchen Jin (1115–234) dynasty has been regarded as a peripheral phenomenon; as such, it remains largely overlooked by traditional historiography. When placed into a broader context, however, both Buddhism under Jin rule and the dynasty itself functioned as a significant link in the long chain of Chinese cultural history. The Jin witnessed a crucial time period during which Chan (Zen) Buddhism, later the most popular Buddhist school in China, gained dominance and began its transmission of several major lines. Jin Buddhism also created a large corpus of material culture, thereby providing invaluable primary sources for the study of Buddhism in China. Based on an analysis of historical writings and archaeological evidence, this article examines the development and various characteristics of Buddhism during the Jin, its relationship with the Jurchen rulers and its influence on the Jin society as a whole. To a large extent, the Jin was at least as important to the development of Buddhism as the Southern Song (1127–276). Moreover, knowledge of Jin Buddhism is indispensable to understanding the Jin culture which, in turn, is essential to understanding the general development of the multifaceted cultural traditions in medieval China.